Fluke Eggs Detection and Classifcation Using Deep Convolution Neural Network - Hongcharoen, Natthaphon; Sanguansat, Parinya; Marukatat, Sanparith (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2022)
We present the experimental results of utilizing object detection to solve the problem of detecting and also classifying the parasite eggs in the fecal slides. We experimented with diﬀerent detection techniques and diﬀerent sizes of the backbone part. The trained models were evaluated using standard mean Average Precision (mAP) on the results from labeled data collected from the closed environment and also manual evaluation on the results from feld data collected from actual medical diagnoses that do not have accurate labels. On the lab data, VFNet achieved a very good 0.897 mAP at the Intersection over Union (IoU) of 0.7 thresholds but performed rather poorly in the classifcation part on the feld data. The relatively older technique Cascade Faster R-CNN had a little below average result in the lab data but had a very good classifcation accuracy on the feld data. The backbone part also had conﬂicting results on the lab data and feld data. The smaller backbones performed better in the lab data but lost to the bigger backbones on the feld data.